CONTRIBUTIONS TO THE DIAGNOSIS OF AUTISTIC SPECTRUM DISORDER: FROM KANNER TO DSM-V - Côrtes, Maria do Socorro Mendes (2020)
The aim of this study is to review the trajectory of the main theoretical concepts and clinical research that contributed to the elucidation and establishment of the diagnosis of Autistic Spectrum Disorder (ASD) in different historical periods, from the main research from the subject, through a non-systematic literature review. Since ASD is a disorder with a multidisciplinary approach, professionals from various fields are involved in its diagnosis and treatment. Know the history behind the diagnosis currently established in the International Classification of Diseases and Health-Related Problems (ICD-10), of the World Health Organization (WHO), and in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), of the American Psychiatric Association (APA) will expand the understanding of ASD.